Effect of low-dose dopamine on depression score in patients with heart failure - Ozmen, Tarik (My University, 2019)
Objectives: This study aimed to assess the effects of low-dose dopamine on patients with depression in theintensive coronary unit.Methods: Relatives of 43 ICU patients enrolled in the study. Sociodemographic characteristics of patients andtheir families recorded. Patients evaluated basal echocardiographic and biochemical values measured in thepatient group. The Beck Anxiety and Depression Scale was used to assess anxiety and depression. Theassessment performed by Beck scale at the 1st and 24th hour.Results: The final study population consisted of 42 patients hospitalized with heart failure. Mean patient agewas 67.5 ± 12.6 years. Average EF was 23.5% ± 8.7% and mean ProBNP was 6343.76 pg/mL in our studypopulation. Changes of before and after dopamine treatment in depression score of heart failure patients wasshowed significantly (before value: 18.95 ± 9.89; after value: 17.29 ± 10.30, p < 0.001) however systolic anddiastolic pressure difference was not significant.Conclusion: Depression increased mortality and hospitalization in patients with heart failure. Therefore, it isan essential trial because of low-dose dopamine improve depression score in intensive care patients. However,prospective studies were needed to assess the long-term efficacy of dopamine.
Keywords: Tıbbi Araştırmalar Deneysel; Kalp ve Kalp Damar Sistemi